(untitled) (Journal of responsible AI & ethics, 2026)
Artificial intelligence (AI) has revolutionized industries, offering opportunities for personalization that enhance user experiences and drive efficiency. However, the use of AI-driven personalization raises significant ethical dilemmas, including concerns around data privacy, informed consent, algorithmic bias, and the potential for manipulation. This paper explores the ethical challenges inherent in AI-powered personalization, particularly in contexts such as e-commerce, social media, healthcare, and education. Through a comprehensive review of literature, case studies, and empirical data, the paper examines the implications of AI-driven personalization on autonomy, justice, and accountability. It also evaluates the ethical frameworks that guide the design and implementation of AI systems, proposing a set of ethical guidelines to mitigate the risks associated with personalization algorithms. Ultimately, the paper argues for a more responsible approach to AI personalization that balances technological innovation with human rights and societal welfare.